2014
DOI: 10.1177/0883073814550312
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphism of Pre-MicroRNA-146a rs2910164 and Serum High-Mobility Group Box 1 With Febrile Seizures in Egyptian Children

Abstract: Interaction between immune-inflammatory process and genetic factors might be implicated in the pathogenesis of febrile seizures. Pre-microRNA (miR)-146a rs2910164 polymorphism is postulated to modulate expression of miR-146a whose anti-inflammatory role involves regulation of high-mobility group box 1. Our aim is to examine whether rs2910164 polymorphism influences serum high-mobility group box 1 levels and whether an association exists between both and febrile seizures. The study included 136 children, divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although previous reports support the hypothesis that miRNAs may contribute to the pathogenesis of epilepsy, studies on the role of microRNAs in the pathophysiology of FS are limited. 5,6,12,13,[17][18][19][20][21][22] Several pro-inflammatory cytokines increase during FS, and, as a consequence, their related miRNAs are also affected. 4,6 Omran et al 7 revealed a negative correlation between IL-1β and miRNA146a expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous reports support the hypothesis that miRNAs may contribute to the pathogenesis of epilepsy, studies on the role of microRNAs in the pathophysiology of FS are limited. 5,6,12,13,[17][18][19][20][21][22] Several pro-inflammatory cytokines increase during FS, and, as a consequence, their related miRNAs are also affected. 4,6 Omran et al 7 revealed a negative correlation between IL-1β and miRNA146a expression.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic polymorphisms might play a role in this correlation. A study conducted by Issac et al 12 revealed that rs2910164 polymorphism in the pre-microRNA-146a gene might be accompanied by an upregulation of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kornblit et al postulated this relationship based on in silico modeling, while others demonstrated it in pneumonia and cancer [ 48 , 49 , 50 ]. Several polymorphisms in gene loci of microRNAs regulating HMGB1 expression were also identified [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex interactions between immune‐inflammatory processes, cytokine activation, and genetic factors play important roles in the development of FS 99,100 . The levels of blood HMGB1 and IL‐1β in children with FS after 30 min of seizure attacks were significantly higher than those with fever only, and these two inflammatory indicators were correlated with each other 101–103 . HMGB1 contributes to the onset of FS and plays an important role in the occurrence of secondary epilepsy associated with the prolongation of FS, 104 and the occurrence of adult epilepsy is related to the recurrence of FS in childhood 105 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 98%